Pengaruh filler carbon black terhadap sifat dan morfologi komposit natural rubber/polypropylene - B Bahruddin; Ida Zahrina; Said Zul Amraini (Jurnal Teknik Kimia Indonesia, 2010)
The effect of carbon black (CB) filler content and mixing technique on tensile properties and morphology of vulcanized natural rubber/polypropylene (NR/PP) blends were studied. The blends were performed in an internal mixer with NR/PP mass ratio of 70/30. The filler was mixed with the blend by two ways. First, CB was mixed with NR in roll-mill before blending with PP in internal mixer and the second, CB, NR and PP were mixed together in internal mixer. The plasticizer and maleated polypropylene (MA-g-PP) compatibilizer were added at constant value with mass fraction of 2% and 5%, respectively. Sulfur was used as curative agent with composition of 3 per hundred rubbers (phr) for the dynamic vulcanization process. The mixing was conducted at 180 oC with the rotor speed of 60 rpm. The morphological study on cryogenically fractured samples was performed using scanning electron microscopy and differential scanning calorimetry. The tensile strength and elongation at break were measured by ISO 527-2 Type 5A standard. The results indicate that the addition of CB as filler could improve the morphology and the properties of the NR/PP blends significantly, especially at CB mass fraction of 30% and blending by first technique. At these condition, tensile strength and elongation at break were found to be 9,8 MPa and 413%, respectively. Keywords: natural rubber, thermoplastic elastomer, carbon black filler, tensile properties, morphology AbstrakPenelitian ini mempelajari pengaruh komposisi dan teknik penambahan filler carbon black (CB) terhadap sifat tensil dan morfologi campuran natural rubber/polypropylene (NR/PP). Sampel campuran disiapkan dengan menggunakan internal mixer pada rasio massa NR/PP 70/30. Filler ditambahkan ke dalam campuran NR/PP dengan komposisi 10%, 20% dan 30% massa. Penambahan filler dilakukan dengan dua cara, pertama dicampur dengan NR terlebih dahulu sebelum pencampuran NR dan PP, dan kedua dicampur bersama-sama NR dan PP dalam internal mixer. Ke dalam campuran juga ditambahkan plastisizer 2% massa dan kompatibilizer MA-g-PP sebesar 5% massa. Proses pencampuran menggunakan metode vulkanisasi dinamik pada suhu 180 oC dan kecepatan rotor 60 rpm. Sebagai curative agent digunakan sulfur dengan komposisi 3 phr (per hundred rubber). Sifat tensil campuran diukur menggunakan standar ISO 527-2 Tipe 5A. Morfologi campuran dianalisa menggunakan scanning electron microscopy. Diperoleh bahwa sifat tensil dan morfologi campuran terbaik diperoleh pada komposisi CB 30% menggunakan teknik pencampuran yang pertama. Pada kondisi tersebut; kuat tarik dan elongation at break campuran masing-masing adalah 9,8 MPa dan 413%.Kata kunci: natural rubber, termoplastik elastomer, filler carbon black, sifat tensil, morfologi